ANALYSIS OF DEVELOPMENT NEEDS VIRTUAL LABORATORY FOR LEARNING VOCATIONAL SCHOOL PRACTICES IN THE PANDEMIC TIME COVID-19 - Bunyamin, Eskawati Musyarofah; Siregar, Eveline Siregar; Kusumawardani, Dwi Kusumawardani (Journal of Education Research and Evaluation, 2021)
During the COVID-19 pandemic, schools did not open face-to-face learning services. The Ministry of Education and Culture has issued a policy learning from Home (BDR) to support the principles of the Education Policy in the COVID-19 Pandemic that the health and safety of students, educators, education personnel, families, and the community is the top priority. However, learning in Vocational School (SMK) is mostly based on practice so that BDR activities cannot be implemented. One thing that is done to overcome this is that some practicum activities can be executed using multimedia known as virtual laboratories. The aim of this study is to conduct a need analysis for the development of a virtual laboratory.Â  Needs analysis is carried out to gather data about gaps and needs as well profiles of students that can be used as a basis or reference in developing virtual laboratory at the next stage. Data collection was carried out by means of observation, interviews, and distributing questionnaires. The results showed that a virtual laboratory was needed to support practical learning for vocational students.